Breaking New Ground? Gifford Pinchot and the Birth of 'Empire Forestry' in the Philippines, 1900-1905. (1st August 2009) - Bankoff, Greg
Abstract : Professional forest management in the Philippines is largely attributed to the ideas and endeavours of American foresters such as Gifford Pinchot, George Ahern and Henry Graves who were instrumental in establishing the Insular Bureau of Forestry in 1900 and in passing the forestry laws of 1904 and 1905. These men, however, did not so much transfer American forest management directly to the archipelago let alone blindly implement empire forestry policies developed in other colonial settings such as British India. Instead, they pragmatically improvised new methods of forest management that were a blend of European, American and local expertise, 'hybrid practices' more suited to an administratively and scientifically unstable tropical setting.